Dialogical-transformative academic supervision model in vocational high school: Systematic literature review - Ervin Rudi Haryadi (Rafandha Press, 2026)
Background: Academic supervision at vocational high schools is primarily defined by administrative and compliance-focused methods, which restrict opportunities for teacher reflection, pedagogical innovation, and ongoing professional growth. This circumstance results in a discordance between supervisory techniques and the evolving requirements of vocational education and industry. Purpose: This study seeks to create a dialogic-transformative academic supervision model by including reflective practice, transformative learning, self-determination theory, and instructional leadership in the realm of vocational education. Method: Utilizing the PRISMA framework, this investigation implemented a systematic literature review (SLR). A total of 327 articles were identified, with 16 articles being selected based on the inclusion and exclusion criteria. To develop a conceptual framework and supervision model, data were analyzed using thematic synthesis, axial coding, and open coding. Findings: The findings show that supervision techniques are fundamentally constrained and hinder reflective and transformative learning. Professional dialogue underpins the study's dialogic-transformative supervision paradigm, which has four interrelated dimensions: reflective, transformational, motivating, and structural. This model theoretically and practically improves vocational school teacher professional development and learning quality through a cycle of reflection, change, and implementation.